Optimizing Selenium Polysaccharide Supplementation: Impacts on Growth, Oxidative Stress, and Tissue Selenium in Juvenile Large Yellow Croaker (Larimichthys crocea) - Jinxing Xiao; Zhoudi Miao; Shiliang Dong; Kaiyang Wang; Fan Zhou; Zilong Li (Animals)
Selenium (Se) is an essential trace element critical for animal growth and immune function. This study investigated the dietary selenium requirement of juvenile large yellow croaker (Larimichthys crocea) through an 8-week feeding trial. Five experimental diets were formulated by supplementing a basal diet with selenium polysaccharides (Se-PS) at 0, 20, 30, 40, and 50 mg/kg, resulting in analyzed Se concentrations of 0.35, 0.54, 0.71, 0.93, and 1.11 mg/kg, respectively. The results demonstrated that growth performance and feed efficiency improved with increasing dietary selenium, peaking at 0.93 mg/kg before declining at higher levels. Antioxidant enzyme activities—superoxide dismutase (SOD) and catalase (CAT)—in serum and liver tissues exhibited a dose-dependent increase, reaching maximal levels at 1.11 mg/kg. Conversely, malondialdehyde (MDA), a marker of oxidative stress, progressively decreased in both serum and liver, attaining its lowest concentration at 1.11 mg/kg, though this did not differ significantly from the 0.93 mg/kg group (p = 0.056). Tissue selenium accumulation was highest at these optimal dietary levels. Based on the growth performance, oxidative stress response, and tissue selenium retention, the recommended dietary selenium requirement for juvenile large yellow croaker is 0.93 mg/kg. These findings highlight the importance of optimal Se supplementation in aquafeeds to enhance growth and physiological health in farmed fish.